Предмет: Алгебра,
автор: TRESAD12
Упростите выражение:
1) (a-b)(a+b)(a⁴+b²+b⁴)
2) (y-3)(y²+3y+9)-y(y-3)(y+3)-(y+3)²
Ответы
Автор ответа:
0
(a-b)(a+b)(a⁴+b²+b⁴)=(a²-b²)(a⁴+b²+b⁴)=a⁶-b⁶
(y-3)(y²+3y+9)-y(y-3)(y+3)-(y+3)²=y³-3³-y(y²-3²)-(y²+6y+3²)=
= y³-27- y³+9y - y²- 6y- 9 = 3y-36=3(y-12)
(y-3)(y²+3y+9)-y(y-3)(y+3)-(y+3)²=y³-3³-y(y²-3²)-(y²+6y+3²)=
= y³-27- y³+9y - y²- 6y- 9 = 3y-36=3(y-12)
Автор ответа:
0
Как вы ставите степень?
Похожие вопросы
Предмет: Алгебра,
автор: Armin5555
Предмет: Алгебра,
автор: tupikdima2000
Предмет: Английский язык,
автор: dianaasyrbaeva444
Предмет: Математика,
автор: Kirillkapro
Предмет: Алгебра,
автор: Аноним